The Effect of Service Quality and Price on Customer Satisfaction - Kevin Indajang; Vivi Candra; Martin Yehezkiel Sianipar; Lenny Dermawan Sembiring; Sudung Simatupang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Consumer satisfaction is the most dominant factor in meeting one of the needs of consumers and factors that can meet consumer satisfaction include service quality and price. Research conducted at Ayam Geprek Idola Pematang Siantar City, the results of the study with the help of SPSS found that the intrument of research variables had valid and reliable criteria. For the coefficient of determination, strong correlation results from service quality and price to consumer satisfaction and have a positive direction coefficient of service quality and price to consumer satisfaction. The results of the hypothesis found that service quality has a positive and significant effect on customer satisfaction, price also has a positive and significant effect on customer satisfaction. With good service quality and good and affordable prices, it will be able to generate customer satisfaction.